2014
DOI: 10.1186/1472-684x-13-25
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved family member perceptions of patient-focused family-centred care during the last 30 days of life using a mortality follow-back survey: does location matter?

Abstract: BackgroundImproving end-of-life care is an important international issue. Recently Nova Scotia researchers conducted a mortality follow-back survey to provide a population-based description of care provided to adults during their last 30 days of life as perceived by knowledgeable bereaved family members. Here we describe the relationship between the location where the decedent received the majority of care during their last 30 days and the informant’s perception of the extent of unmet need, as defined by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 35 publications
5
38
0
1
Order By: Relevance
“…In fact, breathlessness is one of the most common reasons for emergency room visits of patients with advanced cancer receiving palliative care [17]. Moreover, a study exploring the relationship between unmet needs in the last month of life and the site of end-of-life care found that help with breathlessness was more frequently reported as an unmet need by bereaved family caregivers of patients who were cared for at home, than in the hospital [18].…”
Section: Behavioural Responses To Breathlessness: the Influence On Damentioning
confidence: 98%
“…In fact, breathlessness is one of the most common reasons for emergency room visits of patients with advanced cancer receiving palliative care [17]. Moreover, a study exploring the relationship between unmet needs in the last month of life and the site of end-of-life care found that help with breathlessness was more frequently reported as an unmet need by bereaved family caregivers of patients who were cared for at home, than in the hospital [18].…”
Section: Behavioural Responses To Breathlessness: the Influence On Damentioning
confidence: 98%
“…The literature also suggests the presence of a discrepancy between what patients report as their preferred place of death (most often home) and their actual place of death [12][13][14][15][16][17][18][19][20] . Compared with people receiving patient-centred palliative care services at home, those who die in institutions such as acute care facilities have unmet needs for symptom control, physician communication, emotional support, and respectful treatment 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Those criticisms have included lack of expertise and of adequate home support services, lack of coordinated comprehensive programs, fragmentation of care, and inadequate caregiver support. Although eol care has been studied in several provinces 14,22,[33][34][35][36][37][38][39] , the quality of data for comparing eol care in cancer patients across Canada is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of the study include the exceptional agreement with the two NBT definitions that include quality of life and patient self-determination as well as demonstrating providers comfort with being able to differentiate NBT from beneficial treatment with fairly high certainty. Not surprisingly, unrealistic expectations on the part of the patients and their surrogates were felt to be a driving force behind continuing NBT, and there were several variables that demonstrate different perceptions on the part of physicians and nurses; themes that were present 20 years ago (1) and still evident in recent literature (3)(4)(5). Lastly, the proposed solutions are to have better communication, training, and strategies and increased use of advanced care planning.…”
mentioning
confidence: 87%
“…A recent study demonstrated that the addition of a palliative care team to an urban ICU led to earlier hospital discharge and an increased number of hospice admissions and transitions to palliative care (6). Including palliative care as an option leads to an improvement in surrogate and patient perception of end-of-life care (3,6,15).…”
Section: Referencesmentioning
confidence: 98%